The Effect of Kinds of Plant Media Contaminated with Factory Waste on Vegetative Growth of Corn Plant (Zea mays) and Rice Plant (Oriza Sativa) - Sousa , David; Mindari, Wanti; Augustien, Nora (Future Science)
The fabrication industry plays a large role as a source of agricultural land pollution, especially in areas close to factories. Corn and rice plants are food crops that are needed by the community. Along with increasing environmental pollution, research is needed. The purpose of this study was to determine the effect of plant media contaminated with plant waste on the vegetative growth of corn and rice plants. The research was carried out in the greenhouse and laboratory of the Land Resources of the Faculty of Agriculture of the East Java National Veterans Development University. This research uses a completely randomized factorial design with 2 factors. The first factor is the type of plant which consists of 2 factors (corn plants and rice plants). The second factor is the type of media contaminated with factory waste consisting of 6 levels of treatment (paper mills, pharmaceutical factories, trias factories, leather factories, batik factories and garden lands). The results of the treatment were 12 treatment combinations with 3 replications and using the Least Significant Difference test (LSD) of 5%. The results showed that plant media contaminated with factory waste showed a real interaction with the length of the corn plant + paper factory, corn + pharmaceutical factory, corn + trias factory and corn + batric factory at the age of 4 HST. The types of corn plants respond better at the beginning of plant growth, plant length, number of leaves and root length. Rice types give a better response to the number of leaves, tillers, number of tillers and number of roots. The type of pharmaceutical planting media gives a better effect on the parameters of plant length and number of leaves.